MODERATE IMPACT OF GOOD CORPORATE GOVERNANCE IN FINANCIAL PERFORMANCE ON FIRM VALUE - Imang Dapit Pamungkas (UNIB Press, 2022)
This research examines the effect of the firm value, managerial ownership and institutional ownership as moderating variables to moderate the relationship of financial performance to the firm value. This research population uses properties and real estate sector companies listed on the Indonesia Stock Exchange for the period 2017-2020 with a total sample of 193. This type of research is a quantitative research using secondary data. The study used Warp-PLS analysis tool version 7.0. Sampling techniques use purposive sampling that aims to obtain samples that fit the criteria set by the author. Financial performance has no effect on the value of properties and real estate sector companies for the period 2017-2020. The results of this study found that managerial ownership is not able to moderate the relationship between financial performance to the value of the company. However, institutional ownership can moderate financial performance against the firm value in the properties and real estate sectors for the period 2017-2020. Suggestions for further researchers to be able to add other variables that affect the value of the company, using other aspects such as profitability in measuring financial performance. Further researchers can also expand or use research objects other than the properties and real estate sectors to discover the results of different studies.